T2*-Correction in Dynamic Contrast-Enhanced Magnetic Resonance Imaging of Glioblastoma From a Half Dose of High-Relaxivity Contrast Agent. Issue 6 (November 2017) - Filice, Silvano; Crisi, Girolamo; Erb, Gunter
Abstract : Objective: The aim of this study was to evaluate the arterial input function (AIF) and tissue enhancement time curve (tissue function [TF]) obtained after the administration of a half-dose gadobenate dimeglumine (0.05-mmol/kg body weight [bw]) compared with a full dose (0.1-mmol/kg bw) of a standard-relaxivity contrast agent. Methods: We enrolled 40 adult patients with glioblastoma in an interindividual comparative study. Patients were randomized to 1 of the 2 study arms: 20 patients received 0.1-mmol/kg bw of gadoterate; the other 20 patients received 0.05-mmol/kg bw of gadobenate. The patients underwent dynamic contrast-enhanced magnetic resonance imaging examinations. Arterial input function, tissue enhancement time curve (TF), tumor transfer rate (K trans ), and tumor extracellular-extravascular volume fraction (Ve ) were calculated for each patients. Averaged AIF, TF, K trans, and Ve of both groups were compared. Results: A significant difference ( P = 0.001) between the peak AIF values obtained with the 2 different gadolinium-based contrast agents was observed. No difference was found between TFs ( P = 0.35). Comparison on kinetic parameters revealed a significant difference for K trans ( P = 0.047) but no difference for Ve ( P = 0.74). Conclusions: The administration of half dose of the high-relaxivity contrast agent gadobenate is effective in improving AIF by reducing T2*-shortening effects on dynamic contrast-enhanced magnetic resonance imaging and ensuring at the same time an adequate signal enhancement in tumor tissue. The use of 0.05-mmol/kg bw of gadobenate not only is feasible but also can lead to a better estimation of K trans based on a more accurate AIF assessment.